Adult Spinal Deformity: Current Concepts and Decision-Making Strategies for Management - Kim, Hong Jin (Asian Spine J, 2020)
Adult spinal deformity (ASD) is characterized by three-dimensional abnormalities of the thoracic or thoracolumbar spine that exerts significant impacts on the health-related quality of life (HRQoL). With the important effects that deformity of the sagittal plane exerts on the HRQoL, there have been paradigm shifts in ASD evaluation and management. Loss of lumbar lordosis is recognized as a key driver of ASD followed by reducing kyphosis, pelvic retroversion, and knee flexion. The Scoliosis Research Society (SRS)– Schwab classification reflects the sagittal spinopelvic parameters that correlate pain and disability in ASD patients. Although the SRS–Schwab classification provides a realignment target framework for surgeons, a structured patient-specific systemic approach is crucial for the process of decision-making. ASD management should be focused on restoring age-specific harmonious alignment and should consider the comorbidities and risk factors of each patient to prevent catastrophic complications and enhance the HRQoL.